2013
DOI: 10.2147/dddt.s52485
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly targeted drugs for metastatic colorectal cancer

Abstract: The survival rate of patients with metastatic colorectal cancer (mCRC) has significantly improved with applications of molecularly targeted drugs, such as bevacizumab, and led to a substantial improvement in the overall survival rate. These drugs are capable of specifically targeting the inherent abnormal pathways in cancer cells, which are potentially less toxic than traditional nonselective chemotherapeutics. In this review, the recent clinical information about molecularly targeted therapy for mCRC is summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…5G-5L, Supplementary Table ST7, Supplementary Fig. S4G-S4J) consistent with known sensitivity of KRAS WT colon cancer to inhibition of EGFR and approval of cetuximab (35). …”
Section: Resultssupporting
confidence: 75%
“…5G-5L, Supplementary Table ST7, Supplementary Fig. S4G-S4J) consistent with known sensitivity of KRAS WT colon cancer to inhibition of EGFR and approval of cetuximab (35). …”
Section: Resultssupporting
confidence: 75%
“…Progression-free and overall survival in patients with mCRC was improved greatly by the addition of anti-VEGF and/or anti-EGFR to standard chemotherapy, in either first- or second-line treatment. [ 12 , 55 ]. However, several clinical results have suggested that VEGF and EGFR combinatory therapy do not improve the overall prognosis in CRC [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, the process leading to the formation of new blood vessels, plays an important role in tumor development and distant metastasis [ 8 ], and its induction is mediated by numerous angiogenic factors [ 9 ]. Among these factors, vascular endothelial growth factor (VEGF) and its receptors are the most potent molecules activating endothelial cells metastasis and increasing vascular permeability [ 10 12 ]. Inhibition of VEGF activity has been reported to suppress the proliferation of cancer cells and improve the prognosis for unresectable CRC patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While aflibercept is available in a single-use glass vial designed to provide 0.05 ml of 40 mg/ml solution (2 mg) for intravitreal injection, ziv-aflibercept is available as 100 mg per 4 ml (25 mg per ml) solution or 200 mg per 8 ml (25 mg per ml) solution, in a single-use vial. Aflibercept is iso-osmolar, whereas ziv-aflibercept is hyperosmolar (1000 mOsm/l) relative to the vitreous [15, 16]. …”
Section: Fusion Proteins: History Chemistry Production and Biologymentioning
confidence: 99%